Health workers' use of electronic information concerning children with specific communication needs - A M Wium; E Naudé (AOSIS, 2004)
Information regarding young children who experience barriers to the development of listening, language and learning is limited in the South African context. Opsomming In die Suid-Afrikaanse konteks is daar beperkte inligting oor jong kinders vir wie daar struikelblokke is in die verwerwing van luister-, taal- en leervaardighede. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.